2002
DOI: 10.1159/000056055
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Intraventricular Surgery for Treatment of Hydrocephalus and Loculated CSF Space in Children Less than One Year of Age

Abstract: Controversy exists regarding whether children under 1 year of age have a higher risk of treatment failure after neuroendoscopic procedures for the treatment of hydrocephalus than older children. We retrospectively reviewed the surgical management and clinical outcome of 15 infants who underwent neuroendoscopic surgery for the treatment of CSF space loculation and hydrocephalus. We performed 8 third ventriculostomies, 3 endoscopic arachnoid cyst fenestrations, 2 aqueductoplasties, 1 septostomy and in 1 patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…Among these 22 lateral ventricular arachnoid cysts, there were 7 cases of pediatric lateral ventricular arachnoid cysts, all of which occurred in males compared with the authors' case who was female [2,6,8,12,24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among these 22 lateral ventricular arachnoid cysts, there were 7 cases of pediatric lateral ventricular arachnoid cysts, all of which occurred in males compared with the authors' case who was female [2,6,8,12,24].…”
Section: Discussionmentioning
confidence: 97%
“…In the review of 7 pediatric arachnoid cyst cases of the lateral ventricular arachnoid cyst in the literature, the patients were treated with cystoperitoneal shunt in 1 case, fenestration in 2 cases, fenestration and shunt in 2 cases, endoscopic fenestration in 1 case, endoscopic fenestration and shunt in 1 case, and shunt and open removal in 1 case. If the authors' case is included, the combined approach totals 5 cases [2,6,8,12,24]. In the literature that describes 15 adult arachnoid cysts of the lateral ventricle, the patients were treated with open cyst removal in 2 cases, open fenestration or partial cyst removal in 7 cases, endoscopic fenestration in 2 cases, fenestration and shunt in 2 cases, and no treatment in 2 cases [3,5,7,9,11,13,17,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies of ETV in young infants (< 1 year of age) have been published since 1990. 3,7,10,12,22 In patients less than 1 year of age, Javadpour et al 10 observed a success rate of 48%, with the best outcomes in patients with congenital aqueduct stenosis (71%). Koch and Wagner 12 reported a 31% success rate of ETV, whereas Warf, 22 whose surgeries included choroid plexus cauterization, reported a 47% success rate.…”
Section: Discussionmentioning
confidence: 99%
“…2,15,21,28 With the broadening use of neuroendoscopy, it became used in the setting of multiloculated hydrocephalus. 9,10,19,24,25,32,39 The advantage of using an endoscope for visualization in contrast to open cyst fenestration is obvious because it minimizes the size of skull opening, brain retraction and trauma, and facilitates deep access mainly through preformed and existing cavities. One advantage in endoscopic shunt placement is that the surgeon has intraoperative control of the position of the inserted catheters, thereby potentially decreasing the risk of malpositioning.…”
Section: Discussionmentioning
confidence: 99%